Neural corelates of emotional arousal processing in N200 and P300 event-related potential (ERP) components: a study in young adult Malaysian - Murugia, Yogendren (2021)
INTRODUCTION: The event-related potentials were ideally suited for the study of cognitive processes comprising high temporal resolution as it was for the study of the processing of emotional regulation in the whole of neuroscience and psychological field. OBJECTIVE: This study aims to determine the difference of amplitude and latency of N200 and P300 ERP component as evoked by different levels of visual arousal stimulus and to identify which part of the brain was involved in emotion processing. METHODOLOGY: A total of 30 participants between age of 18-24 years old participated for this cross-sectional study which were recruited from Universiti Sains Malaysia, Health Campus, Kubang Kerian, Kelantan. Affective visual stimuli were chosen randomly from the international affective picture system (IAPS) based on the normative value given and the pictures were grouped into 3 levels of arousal (low, moderate, and high). An event-related potential (ERP) recording using 128 HydroCel Geodesic Sensor Net was done on participants during the passive viewing of the affective visual stimuli. RESULTS: A non-parametric test (Friedman test) indicated that all the midline electrodes (Fz, Cz, Pz, and Oz) were statistically not significant (p>0. 05) with regards to different arousal levels of affective visual stimuli (low, moderate, and high), except for electrode Cz N200 latency a statistically significant result was shown (x2 = 12. 940, df = 2, p = 0. 002). Hence, follow up post hoc analysis using there was no statistically significant difference between N200 latency Cz low and Cz high (z = -1. 78, p = 0. 075) or between the Cz moderate and Cz high (z = -1. 190, p = 0. 234). However, Wilcoxon post hoc test indicated that the low arousal (mean rank = 1. 53) was perceived as significantly more aroused (shorter time were taken) than the moderate arousal, in which the latency was longer for Cz electrode (mean rank = 2. 45, t = 79, z = -2. 83, p = 0. 005). There were no differences for source localization between both N200 and P300 ERP components which was found to be located in the temporal lobe but with a separate Broadmann area (BA). In addition, low and moderate arousal was found in the BA 20 while high arousal was found in the BA 38. CONCLUSION: Low arousal images display a higher stimulation compared to moderate and high images. This is because it includes memory that we call as priming under implicit memory (recognition task). Besides, we can say that different individuals respond differently to each situation, since the brain is still controlled. Some people will need a greater degree of stimulation, which would inspire them to look for relaxing and enjoyable experiences. Others may do best at low levels of arousal, and may feel motivated to look for calming and stimulating tasks.